Initial Teacher Training, Practical Knowledge and Lesson Study, a perfect trio. Case Study. - Rodriguez-Robles, Cristina; Soto-Gómez, Encarnación (My University, 2018)
This paper focuses in analysing the possibility of reconstructing practical knowledge by incorporating Lesson Study (LS) in the Practicum III and the Final Dissertation in initial training for infant school teachers at Málaga University, Spain. The research has a qualitative approach, which is articulates through a case study. It achieved this by working with a group of five infant education undergraduates as they developed the Practicum III and Final Dissertation subjects. These subjects are studied during different terms, but are merged and articulated through the Lesson Study. Findings/Conclusions: - Introducing students to a complex, unknown learning context such as that posed by the LS brings out their practical knowledge, provoking the constant awakening of practical thinking. -The phases of the LS place María in a reflective dialogue between practice and theory, bringing about two key processes for the reconstruction of practical knowledge: theorisation of practice and experimentation of theory. - Cooperation and academic tutoring was a challenge and a trustworthy platform that allowed her to break away from traditional pedagogical conceptions and bring her espoused theories to life, enjoying the coherence of coordinating her espoused theories and her theories-in-use, and seeing how children communicated and cooperated autonomously.
Keywords: Didáctica; Formación inicial docente; Lesson Study; Investigación-acción colaborativa; Practicum; Trabajo de Fin de Grado; Conocimiento práctico docente; Desarrollo profesional docente